2014
DOI: 10.1177/102490791402100607
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dominant Hand Position during Chest Compression by Novice Rescuers: An Observational Simulation Study

et al.

Abstract: Introduction The aim of this study was to determine the effect of hand positioning on the quality of external chest compression (ECC) by novice rescuers. Methods This observational simulation study was conducted for 117 included participants. After completion of an adult cardiopulmonary resuscitation (CPR) training program for 3-h, the participants selected which of their hands would be in contact with the mannequin during ECC and performed 5 cycles of single rescuer CPR on a recording mannequin. The participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…The present study investigated individual components of the overall ECC performance, those being ECC depth, ECC rate and ECC release (recoil). With regard to handedness and ECC depth, the present study's result of no difference is consistent with the majority of existing data (4)(5)(6)9), but in contrast to Wang et al and Kundra et al who found more optimal depth being achieved when the dominant hand was on the chest (7,8).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study investigated individual components of the overall ECC performance, those being ECC depth, ECC rate and ECC release (recoil). With regard to handedness and ECC depth, the present study's result of no difference is consistent with the majority of existing data (4)(5)(6)9), but in contrast to Wang et al and Kundra et al who found more optimal depth being achieved when the dominant hand was on the chest (7,8).…”
Section: Discussionsupporting
confidence: 92%
“…With regard to handedness and ECC rate, the present study finding of no difference challenges results from three earlier simulation studies that both reported significant differences favouring dominant hand on the chest evidenced by higher mean compression rates (4)(5)(6). While DHOC resulted in significantly higher mean rates, the rates of both groups in each study were comfortably within the recommended guideline parameters for effective ECC raising the question of whether the reported differences would be clinically significant.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In other words, right-handedness or left-handedness did not affect the depth of chest compression during resuscitation. However, Jo et al 12 suggest that ECC in the group that used dominant hand was significantly faster than the group that used non-dominant hand. The contact of the dominant hand with the chest can affect the depth of chest compression.…”
Section: Discussionmentioning
confidence: 97%